KEPENTINGAN INDONESIA MELAKUKAN IMPOR KACANG KEDELAI DARI AMERIKA SERIKAT TAHUN 2018-2020 - Nurul Laili Sari; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The United States is the largest trading partner. United States Soybean agricultural industry is one of Indonesia's import destinations. With a significant increase in soybean imports between Indonesia and the United States, the bilateral relationship between Indonesia and the United States will be strengthened and soybean imports will be strengthened. Therefore, to examine why Indonesia imports soybeans from the United States in 2018-2020. This research is based on the theory of interdependence, in the level of analysis of countries and nations. The state as one of the actors in the International Association. Which is a country, namely Indonesia and the United States which carry out bilateral cooperation in the economic and political fields. Data was collected using qualitative methods, with data sourced from primary data from interviews and official websites, books and journals discussing imports of Indonesian and United States soybeans. The results show that Indonesia's interests in importing soybeans from the United States in 2018-2020 consist of two interests, namely economic interests and political interests. Economic interests consisting of local soybean production do not meet domestic needs, increasing domestic demand, and the price of imported soybeans is cheaper than local soybeans. And political interests which consist of maintaining good relations between Indonesia and the United States, the United States is the second largest trading partner in Indonesia, and opportunities for exporting Indonesian products to the United States. Keywords: Imports, Soybeans, Indonesia-United States, Economi and Political Interests, 2018-2020